Self-Efficacy, engagement, and spiritual intelligence on performance via OCB among Jakarta educators - Pujiati, Herni; Feani, Dewi Puspaningtyas; Cahaya, Yohannes Ferry (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the influence of self-efficacy, employee engagement, and spiritual intelligence on Organizational Citizenship Behavior (OCB), as well as to examine the role of OCB in enhancing the performance of part-time teachers in Jakarta. Research Methodology: This quantitative research used a survey method, collecting data from 278 village officials in Brebes Regency through questionnaires. Structural Equation Modeling (SEM) with Partial Least Square (PLS) was employed for data analysis to test both direct and indirect effects among variables. Results: The findings reveal that ethical leadership, organizational commitment, and work culture significantly influence job satisfaction. Moreover, job satisfaction positively and significantly affects village officials' performance. Ethical leadership and work culture also directly affect performance, while organizational commitment's direct effect on performance was not significant. However, job satisfaction successfully mediates the influence of organizational commitment on performance. Conclusions: This study found that spiritual intelligence significantly influences Organizational Citizenship Behavior (OCB), which in turn positively affects the performance of part-time teachers in Jakarta. However, self-efficacy and employee engagement showed no significant effect on OCB. The findings highlight the key role of spiritual intelligence in enhancing teacher performance through OCB. Limitations: The study is limited to village officials in Brebes Regency, making generalization to other regions or administrative contexts less applicable. The use of cross-sectional data limits the ability to observe changes over time. Additionally, self-reported questionnaires may introduce response bias, affecting the objectivity of the data. Contribution: The study is limited to village officials in Brebes Regency, making generalization to other regions or administrative contexts less applicable. The use of cross-sectional data limits the ability to observe changes over time. Additionally, self-reported questionnaires may introduce response bias, affecting the objectivity of the data.